2008
DOI: 10.1016/j.alcohol.2008.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alcohol and saccharin deprivations on concurrent ethanol and saccharin operant self-administration by alcohol-preferring (P) rats

Abstract: Consumption of sweet solutions has been associated with a reduction in withdrawal symptoms and alcohol craving in humans. The objective of the present study was to determine the effects of EtOH and saccharin (SACC) deprivations on operant oral self-administration. P rats were allowed to lever press concurrently self-administer EtOH (15% v/v) and SACC (0.0125% g/v) for 8 weeks. Rats were then maintained on daily operant access (non-deprived), deprived of both fluids (2 weeks), deprived of SACC and given 2 ml of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…Although the possibility exists that what appears to be an increase in consumption as a result of deprivation is in fact merely an alteration in baseline consumption over time, several studies (reviewed in Rodd et al, 2004) indicate that baseline consumption, in similar operant conditions as the present study, is stable and does not increase over a period of several weeks (Toalston et al, 2008). With regard to the effect of treatment on baseline self-administration, because the saline-treated rats increase ethanol self-administration from baseline and the treatments reduced self-administration compared with saline, it can be concluded that NAL and LY are inhibiting ethanol self-administration under relapse conditions.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Although the possibility exists that what appears to be an increase in consumption as a result of deprivation is in fact merely an alteration in baseline consumption over time, several studies (reviewed in Rodd et al, 2004) indicate that baseline consumption, in similar operant conditions as the present study, is stable and does not increase over a period of several weeks (Toalston et al, 2008). With regard to the effect of treatment on baseline self-administration, because the saline-treated rats increase ethanol self-administration from baseline and the treatments reduced self-administration compared with saline, it can be concluded that NAL and LY are inhibiting ethanol self-administration under relapse conditions.…”
Section: Discussionmentioning
confidence: 53%
“…Female P rats were used throughout the study because females were available when the study was initiated. Although estrous cycle was not monitored, previous studies carried out with female P rats, in which ethanol motivated responding (ethanol consumption and intracranial ethanol self-administration) was monitored over a 2–4-week period, indicated no significant day-to-day alterations in responding, suggesting little influence of the estrous cycle on motivated responding by female P rats (Rodd et al, 2005; Sable et al, 2006; Toalston et al, 2008). Rats were maintained on a 12-h reversed light-edark cycle (lights off at 0900 h).…”
Section: Methodsmentioning
confidence: 97%
“…P rats operantly self-administer ethanol intragastrically for its post-ingestive effects (Murphy et al, 1988; Waller, McBride, Gatto, Lumeng, & Li, 1984). P rats will operantly self-administer ethanol using a dipper model, indicating these rats will work for access to ethanol (Files, Samson, Denning, & Marvin, 1998; Murphy, Gatto, McBride, Lumeng, & Li, 1989; Rodd et al, 2003; Rodd-Henricks et al, 2002a, 2002b; Samson, Files, Denning, & Marvin, 1998; Toalston et al, 2008) or sipper tube model (Beckwith & Czachowski, 2014; Bertholomey, Verplaetse, & Czachowski, 2013; Czachowski & Samson, 2002; Samson & Czachowski, 2003; Verplaetse, Rasmussen, Froehlich, & Czachowski, 2012; Verplaetse & Czachowski, 2015) indicating these rats will work for access to ethanol.…”
Section: The P Rat As a Genetic Animal Model Of Alcoholismmentioning
confidence: 99%
“…The mean number of daily 1 hr sessions required for a P rat to acquire saccharin (0.0125% w/v) self-administration is about 10–13 (Toalston et al, 2008; current data set), while 95% of P rats will acquire operant oral self-administration of 15% EtOH in 4 sessions (Rodd-Henricks et al, 2002; Toalston et al, 2008, current data). In contrast, it takes approximately 19 daily sessions for 85% of P rats to acquire consistent saccharin self-administration (Toalston et al, 2008; current data). Therefore, it is impractical to examine the effects of compounds on the acquisition of saccharin self-administration in P rats.…”
Section: Methodsmentioning
confidence: 95%
“…P rats acquire saccharin self-administration at a slower, less uniform rate than EtOH (Toalston et al, 2008). The mean number of daily 1 hr sessions required for a P rat to acquire saccharin (0.0125% w/v) self-administration is about 10–13 (Toalston et al, 2008; current data set), while 95% of P rats will acquire operant oral self-administration of 15% EtOH in 4 sessions (Rodd-Henricks et al, 2002; Toalston et al, 2008, current data).…”
Section: Methodsmentioning
confidence: 99%